ISOLATION AND CHARACTERIZATION OF FLAVONOID COMPOUNDS FROM ETHYL ACETATE FRACTION OF Macaranga hosei LEAVES - Frenki Alan Nuari; Eva Marliana; Daniel Daniel (Jurusan Kimia FMIPA UNMUL, 2019)
Isolation and characterization of flavonoid compounds in the third fraction of ethyl acetate of Macaranga hosei leaves. The separation process in the third fraction of ethyl acetate was perfomed using gravity column chromatography with gradient elution method. The obtained isolate was tested for its purity using thin layer chromatography with various eluents named n-hexane, chloroform, acetone, ethyl acetate and methanol with Rf values 0; 0,17; 0,86; 0,97 and 0,81 respectively. The isolate was characterized as MH-1 phenolic compound as much as 30 mg in the form of oil. Analysis of MH-1 compound with UV showed 2 peaks at ? 295 nm (band II) and 340 nm (band I). Analysis of MH-1 compounds with FT-IR showed OH functional groups, aliphatic C-H, aromatic C-H, C=O, aromatic C=C, C-O-C and C-OH. Based on the results of the UV and FT-IR spectra, the MH-1 compound is assumed to be of flavonoids.